Sistem Pendukung Keputusan Pemilihan Guru Kompetensi Terbaik Menggunakan Metode MOORA - Ardinsah Ardinsah (Bulletin of Information System Research, 2024)
This research was conducted to conduct the process of selecting the best computer competency teacher at SMK Dwiwarna Medan. The assessment stage for selecting the best computer competency teacher aims to reward the best computer competency teacher at SMK Dwiwarna Medan. This study uses a Decision Support System (DSS) which is used as a system that can process the assessment of the best teacher competencies. At the stage of selecting the best computer competency teacher, there are 5 criteria, namely Hardware Skills, Software, Networking Skills, Communication Skills, and Creativity. Therefore we need a system that is able to make decisions, namely DSS using the MOORA method to get a preference value from the selection of the best computer competency teacher, there is the best alternative on the A3 alternative on behalf of Joko Suprinato with a value of 0.5123.